2021
DOI: 10.1080/00981389.2021.1885560
|View full text |Cite
|
Sign up to set email alerts
|

Self-care among healthcare social workers: The impact of COVID-19

Abstract: For social work practitioners in healthcare settings, self-care can be an integral tool to assuaging stressors associated with COVID-19. However, research that examines the impact of public health crises, such as COVID-19, is nominal, at best. This exploratory study investigated the impact of COVID-19 on the self-care practices of self-identified healthcare social workers (N = 2,460) in one southeastern state. Primary data were collected via an electronic survey and assessed via a retrospective pre/post design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 42 publications
0
31
0
2
Order By: Relevance
“…These changes could have a negative psychological impact due to prolonged stress, higher job demands, changing responsibilities and limited resources worsened by the COVID-19 pandemic (Harrikari et al 2021;Holmes et al 2021;Miller and Reddin Cassar, 2021). These stresses highlight possible reasons for the deterioration between Phases 1 and 2 within this present study.…”
Section: Summary Of Findings and Comparison With Other Literaturementioning
confidence: 68%
See 1 more Smart Citation
“…These changes could have a negative psychological impact due to prolonged stress, higher job demands, changing responsibilities and limited resources worsened by the COVID-19 pandemic (Harrikari et al 2021;Holmes et al 2021;Miller and Reddin Cassar, 2021). These stresses highlight possible reasons for the deterioration between Phases 1 and 2 within this present study.…”
Section: Summary Of Findings and Comparison With Other Literaturementioning
confidence: 68%
“…Compassionate employers, and a positive, supportive workplace could overcome the pressure in social work and care work and improve wellbeing and work-related quality of life(Cook et al 2020;Kalliath et al 2020). Other means of achieving a better work-life balance to improve wellbeing must involve a health-promoting lifestyle with training and development opportunities, self-care, flexible working hours and less excess demands and working responsibilities(Miller and Reddin Cassar, 2021) Kalliath et al (2020). have suggested that by promoting work-family measures among the social care workforce, this can contribute to positive work outcomes.…”
mentioning
confidence: 99%
“…Burnout was evaluated with a validated single‐item burnout measure with a five‐point Likert scale 23 ; responses were dichotomized as a score less than or equal to 2 and a score equal to or greater than 3, with higher scores indicating greater potential symptomatology 24 . Utilizing a retrospective pre/post design, 25,26 participants were asked to rate their level of burnout prior to the pandemic (i.e., about 6 months prior), as well as at the time of completing the survey. The Patient Health Questionnaire‐4 (PHQ‐4), 21 a screen for anxiety and depression, was utilized to measure psychological distress 27,28 .…”
Section: Methodsmentioning
confidence: 99%
“…Hence, we can conclude that health care has a social and self-esteem perspective. Miller and Reddin (2021) associate self-actualization with the realization of self-care to remain healthy.…”
Section: Validation Of Findingsmentioning
confidence: 99%